Beyond Bacteria: The Impact of Protozoa on Periodontal Health - Bruno Pires Miranda; Marcos Tobias de Santana Miglionico; Rhagner Bonono dos Reis; Júlia de Castro Ascenção; Helena Lúcia Carneiro Santos (Microorganisms)
Until recently, bacterial species were the primary etiological factor of periodontal disease, but recent studies have shown that their effective removal from tooth surfaces does not necessarily prevent the progression of the disease. A logical hypothesis leads to the conclusion that various etiological factors contribute to the etiopathogenesis of this disease. Recent evidence also indicates protozoa as potential pathogens. In this review, the role of Entamoeba gingivalis, Acanthamoeba spp., and Trichomonas tenax in periodontal disease was analyzed, and the various aspects of the role of protozoa in the etiopathogenesis of periodontal disease, the bacterial–protozoa model of the disease, and the therapeutic implications were categorized. The multifactorial nature of periodontal disorders requires further research to better identify individuals at risk and prescribe earlier and more definitive treatments. The evidence supporting the role of protozoa in periodontal disease is compelling. These organisms are essential contributors to this complex disease. The key to developing more effective prevention and treatment strategies lies in understanding the intricate interactions between protozoa, bacteria, and the host. A better understanding of the protozoa aspect of periodontal disease progression could significantly change the future perspective of diagnosing, preventing, and treating periodontal disease.